(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The aim of this study was to study the waste-water generation through various sources and to suggest the necessary remedial measures so that it generation can be lowered as well as the generated waste water can be re-used .Industrial and municipal sources both contribute to wastewater creation. Initially, as growth and industrialization progressed, industrial wastewater generated a substantial amount of wastewater, whereas municipal wastewater generated a smaller amount. Wastewater generated by the industrial sector has been captured, treated, and recycled throughout time as a result of rising environmental activism, making it sustainable by its use in the majority of sectors. Due to the exponential growth of urbanisation, municipal sewage has increased throughout time, leaving an inextricable impact on urban perennial water sources such as surface riverine and ground water treatment. According to census data from 2011, Jammu and Kashmir has a population of 1.25 million people, up from 1.01 million in 2001. After 2012, the population began to fall, and calculations relating to population growth beginning in 2012 resulted in an average population growth rate of 2.02% each year. According to estimates from the Central Pollution Control Board (CPCB), 85 litres per capita per day (LPCD) of wastewater delivered to each household is returned in the form of sewage. It’s estimated that with an increase in population consuming water and decreasing waste water recycling and reuse in the municipal sector, this might rise to 121 LPCD by 2030. Based on the CPCB estimates, approximately 62 percent of total daily water supply, or 187 MLD of water, is created as city sewage or urban sewage. According to CPCB records, Class I cities received a total water supply of 267.42 MLD in 2010, while Class II cities received a total water supply of 34.24 MLD. This brings the total amount of water supplied to its residents to 301 MLD.